TREATMENT OF URINARY OUTFLOW OBSTRUCTION - Nina Battelino; Damjana Ključevšek; Daša Šfiligoj Planjšek; Tomaž Ključevšek; Robert Kordič (The Society for Children with Metabolic Disorders, 2023)
Urinary outflow obstruction in childhood has various causes. If left untreated several consequences or even kidney injury can occur. With respect to the level of obstruction, an upper (pieloureteral stenosis - PUS, vesicoureteral stenosis - VUS, ureterocoele and ectopic urether) or lower urinary tract obstruction (posterior urethral valve - PUV) can be characterized. The treatment consensus must be reached among different specialists upon careful examination of the results and thereafter the parents have to be thoroughly informed about the decision. We can either decide on radiological intervention or surgical treatment, most frequently a combination of both. The results are generally good, but we must bear in mind that in more serious anomalies, the deterioration of kidney function is in the best case postponed and a further follow-up is mandatory.